SISTEM MULTIPLE CROPPING TANAMAN SAYURAN SEBAGAI ALTERNATIF PENINGKATKAN PENDAPATAN PETANI DI CURUP UTARA REJANG LEBONG - Dwi Fitriani; Fiana Podesta; Ririn Harini (DHARMA RAFLESIA, 2016)
The events have been held in farmer Group Manggala Curup Village and farmer Group Melati Siguring Village, Sub-district North Curup, District Rejang Lebong. Most of farmers in Curup Village and Seguring Village, Sub -district North Curup, plant vegetable plants in monoculture and do not us e a good quality of seed. Farmers have good potential to improve the result and the income with avoiding crop failures or the plummeted of market price. These things will be able to be covered by other plants that can be obtained with intensive use of land by using multiple copping to vegetable plants that have high economy and use of good quality of seeds. The purpose of doing training are (1) farmer group has knowledge about intensification of land using multiple cropping and good quality of seeds (2) farmers are able to be producer of seeds in order to decrease the cost incurred in the next growing season and increace the income. The methods that will be used in training are (1) counselling and education about the agriculture of multiple cropping, good quality of seed, and the way to get good quality of seeds (2) production of demonstration plot (demplot) trial to apply multiple cropping and good quality of seeds. (3) Mentoring system of farmer group. The result of the activity is being able to improve insight of farmer, in the terms of intensification land by using multiple cropping and good quality of seeds. Besides that, farmers can produce their own seeds to the next growing season. The income of farmers in multiple cropping systems of vegetable plants will be higher if it is compared with monoculture system.Keywords: vegetable plant, multiple cropping, good quality of seed